The Problem of Multiculturalism and National Tolerance in Foreign Psychological Theory - Korol, L. D. (Psychological Prospects Journal, 2012)
The article is devoted to considering the problem of multiculturalism and national tolerance in accordance with foreign psychological theories. The analysis concerning these issues is given through the prism of studying such psychological phenomena as national identity and identification, group identity, and acculturation strategies as well. The article also deals with the description of multiculturalism semantic essence and its function models.